The Relationship Between Instructors' Teaching Skills and The Learning Outcomes of The Learning Community at PKBM Surya Padang - Egrina Elfa; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
The Relationship Between Instructors' Teaching Skills and the Learning Outcomes of the Learning Community at PKBM Surya, Padang City. Thesis. Faculty of Science Education. Padang State University. This research is motivated by the low learning outcomes of citizens learning to attend sewing training at PKBM Surya, Padang city. This is presumably because it has something to do with the teaching skills of PKBM instructor Surya, Padang city. This study aims to describe the teaching skills of instructors, learning outcomes of learning citizens in the learning environment, and the relationship between instructor teaching skills and sewing learning outcomes of learning residents at PKBM Surya Kota Padang.This type of research is quantitative research that is descriptive correlational. The population of the study were all 20 learning citizens who attended sewing training at PKBM Sury Padang city and respondents, namely all residents learning embroidery training, with the sampling technique used was a quota sampling. The data collection technique is in the form of a questionnaire with the data collection tool in the form of a questionnaire. The data analysis technique in this study used the percentage formula and Spearman rho correlation.The results of this study show that the teaching skills of the instructor are not good, the learning outcomes of learning citizens to sew are low, and there is a significant relationship between the teaching skills of the instructors and the learning outcomes of learning citizens in PKBM Surya Padang city, this is evidenced by the results of the calculation of the correlation using the Spearman rho formula. which is indicates that rcount (0.619) is greater than rtable at both the 5% confidence level (0.450) and the 1% confidence level (0.591). It is suggested that the PKBM Surya institution provide a conducive learning environment so that participants are motivated to attend embroidery training.Keywords: instructor teaching skills, citizen learning outcomes